A STUDY OF THE GAPS IN IMPLEMENTING SKILL PROGRAMMES IN SIKKIM - Anita Gupta, Dr. Ajeya Jh, Dr. Neeta Dhusia Sharma, Saibal Kumar Saha,PhD Scholar, Professor, Associate Professor, Assistant Professor (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Purpose The objectives of the research is to identify the implementation gaps of skill development programmes in Sikkim. A subsidiary objective is to find if significant beliefs exist across stakeholders in this respect. Design/methodology/approach The research is exploratory and empirical. Primary data was collected as per the belief of stake holders - students, teachers, parents, industry partners and policy-makers on a continuous scale. The sampling frame includes all the 4 districts of Sikkim. T test, ANOVA and score ranking methods were used for the analysis of data. Findings The survey score card revealed that the most discouraging factor was poor attitude and lack of value for skill trainings among the youth. The teachers reported that the most important factor for discouraging the students was that the duration of course was less. Students believed that the most crucial factor for de motivating them was their own attitude and lack of values for skill courses. Research limitations/implications The State and its implementing agencies should focus more on imparting professional counseling and training workshops to enlighten the employable youth in all the Districts of Sikkim and their parents about the importance and utility of such trainings. Originality/value The study indicates that the most significant reason across all stakeholders is poor attitude and lack of values towards acceptance of vocational skill trainings in the State of Sikkim. The study highlights A STUDY OF THE GAPS IN IMPLEMENTING SKILL PROGRAMMES IN SIKKIM PJAEE, 17 (7) (2020) 4273 the demotivate factors of skill development programmes from the perspective of different stakeholders and shows the significance of same with respect to age and cast.